Analisis Economic Value Added (Eva), Profitabilitas, dan Market Value Added (MVA) sebagai Alat Ukur Financial Performance - Valencia Aviliani, Imelda; Nusantoro, Jawoto; Retnaning Rahayu, Sri (Universitas Muhammadiyah Metro, 2025)
The purpose of this research is to analyze financial performance measured through the analysis of economic value added (EVA), profitability, and market value added (MVA) in tobacco companies listed on the Indonesia Stock Exchange. This research uses secondary data, which was collected through documentation methods.The data used in this research comes from the balance sheets and income statements of tobacco companies from 2021–2023, which can be accessed at www.idx.co.id.The purposive sampling method was used with several criteria, resulting in 4 tobacco companies.The results of this study indicate that based on the EVA analysis of tobacco companies for the period 2021-2023, there are 2 companies with positive values, namely the companies with stock codes HMSP and WIIM.Based on the results of the profitability analysis of tobacco companies for the period 2021-2023, the outcome is positive or good.Next, for the MVA analysis of tobacco companies for the period 2021-2023, there are 2 companies with positive values, namely the companies with stock codes HMSP and WIIM.